Inpatient-tailored diabetes self-management education and short-term glycemic change in type 2 diabetes: A pilot case series from RSUD dr. Darsono Pacitan - Arifah, Kun; Widiastuti, Agung; Ernawati, Ucik; Dwi Kurniawan, Yanti (Avicenna : Journal of Health Research, 2026)
Background: Type 2 diabetes mellitus (T2DM) commonly presents with uncontrolled hyperglycemia among inpatients, where self-management gaps compound clinical instability. Diabetes Self-Management Education (DSME) is recommended, yet evidence for inpatient-tailored, short-horizon DSME remains limited. Objective: To evaluate the short-term effect of a ward-adapted DSME adjunct on capillary blood glucose and self-management behaviors in hospitalized adults with T2DM. Methods: purposive sampling (n=2) in the Wijaya Kusuma Inpatient Ward, RSUD dr. Darsono (July-August 2025). The intervention comprised individual bedside DSME (two sessions; 60-90 minutes total) plus discharge reinforcement, delivered by diabetes-trained nurses. Primary outcome: change in capillary glucose (mg/dL) from baseline to post-intervention over 4 days with consistent testing conditions. Secondary outcome: Diabetes Self-Management Questionnaire (DSMQ-16; 0-64). Analyses emphasized descriptive trajectories; exploratory paired t-test/Wilcoxon and bootstrap 95% CIs were reported with α=0.05 (hypothesis-generating). Results: Baseline glucose was 837 and 511 mg/dL; by day 4, values declined to 130 and 120 mg/dL, respectively (absolute change -707 [-84.5%] and -391 [-76.5%]); no hypoglycemia/adverse events occurred. DSMQ-16 improved from 15 to 50 and 17 to 60 (poor to good). Exploratory tests were underpowered (paired t=3.47, p=0.18; Wilcoxon p=0.25), but the effect size was very large (Cohen’s d=2.46), consistent with observed trajectories. Conclusion: A ward-tailored DSME delivered over four days was feasible and associated with rapid, clinically meaningful glycemic improvement and substantial gains in self-management among acutely uncontrolled inpatients with T2DM. Findings are hypothesis-generating and support larger, controlled studies to confirm efficacy, durability post-discharge, and scalability.